Dynamics of incidence and prevalence of type 1 diabetes mellitus in children in the Russian Federation (2001-2007) - Tatiana Yur'evna Shiryaeva; Ekaterina Andreevna Andrianova; Yury Ivanovich Suntsov (Сахарный диабет)
Aim. To study dynamics of main epidemiological characteristics (incidence and prevalence) of type 1 diabetes mellitus (DM) in children in theRussian Federation (RF) and its Federal districts (FD) in 2001-2007. Materials and methods. Analysis of main epidemiological characteristics (incidence, prevalence, mortality) of type 1 DM in children of RF has beenunderway in the Institute of Pediatric Endocrinology, ERC, since 2001 based on results of questionnaire studies. The questionnaires regularly distributedamong Health Committees of RF subjects (primary sources of information) are designed to collect data on the size, age and sex compositionof childrens populations affected by DM1 and the number of newly diagnosed cases as per the end of each reporting year. The data obtainedare compared with those stored in the State Diabetes Registry (secondary source of information). Results. Major trends in the dynamics of epidemiological characteristics of type 1 DM in children of RF are similar to those worldwide. Mean annualgrowth rate is 2,8%. The incidence of DM1 remains highest in the North-West FD (15,66 per 100 000 children) followed by Central andVolga FDs (12,82 and 10,6 respectively) where its is close to the average value FDr RF (11,01). The incidence of DM1 continues to decrease in theSouthern FD (6,61% per year) and undergoes up-and-down fluctuations in Ural and Siberian FDs. It steadily grows in the Far East FD. TheNorth-South gradient of DM1 morbidity across the territory of RF has persisted during the study period. Conclusion. Monitoring main epidemiological characteristics of type 1 diabetes mellitus in children of RF is an integral component of the organizationof medical and preventive aid to these patients that creates a basis for predicting morbidity, planning measures for its control, and improvinggeneral quality of healthcare provided to diabetic children